Cancer‐related fatigue and self‐care agency: A multicentre survey of patients receiving chemotherapy. Issue 23 (11th September 2019) - O'Regan, Patricia; McCarthy, Geraldine; O'Reilly, Seamus; Power, Derek; Bird, Brian Healey; Murphy, Conleth G.; Hegarty, Josephine
Abstract: Aims and objectives: To measure cancer‐related fatigue (CRF), self‐care agency (SCA) and fatigue self‐care strategies, and to explore the relationship between CRF and SCA. Background: Cancer‐related fatigue has been consistently rated as the most elusive, common and severe of symptoms that patients with cancer undergoing chemotherapy experience. Despite its frequency and severity, CRF is poorly managed. A renewed focus on supporting self‐care among patients with cancer has been found to reduce symptom burden, empower patients and improve patient satisfaction. Understanding the link between self‐care agency (i.e. capability and willingness to self‐care) and CRF levels will help practitioners to better support individuals on the cancer journey. Design: A descriptive, correlational survey design was employed. Methods: Patients ( n  = 362) undergoing chemotherapy with a primary diagnosis of breast, colorectal, Hodgkin's and non‐Hodgkin's lymphoma cancers were recruited from four oncology centres in one city in the South of Ireland. Participants completed the Piper Fatigue Scale‐Revised, Appraisal of Self‐care Agency Scale and a researcher‐developed Fatigue Self‐Care Survey. Multivariate logistic regression was used to examine the relationship between CRF and self‐care agency using a dichotomous dependent variable score of four as the cut‐off between those deemed to be fatigued (≥4) and those not fatigued (<4). As recommended by the EQUATOR Network, the STROBE checklist of items for cross‐sectional studies is used to report the study. Results: The incidence of CRF was high with 75% of participants scoring clinically relevant CRF. Higher SCA (OR = 0.96, 95% CI = 0.93–0.99, p  = .011) was associated with decreased odds of developing CRF. Having non‐Hodgkin's lymphoma (OR = 3.02, 95% CI = 1.29–7.07, p  = .011) was associated with increased odds of developing CRF. Conclusions: Patient's undergoing chemotherapy experience significant fatigue. Higher capability for self‐care is associated with lower fatigue. The promotion of SCA and self‐care strategies can impact on CRF. Relevance to clinical practice: Understanding the link between self‐care abilities and fatigue can lead to more individualised and tailored approaches to CRF.